The Association of Myo-Inositol and Selenium Contrasts Cadmium-Induced Thyroid C Cell Hyperplasia and Hypertrophy in Mice - Benvenga, Salvatore; Micali, Antonio; Ieni, Antonio; Antonelli, Alessandro; Fallahi, Poupak; Pallio, Giovanni; Irrera, Natasha; Squadrito, Francesco; Picciolo, Giacomo; Puzzolo, Domenico; Minutoli, Letteria (Frontiers in Endocrinology, 2021)
Previous studies have demonstrated that, in addition to inducing structural changes in thyroid follicles, cadmium (Cd) increased the number of C-cells. We examined the effects of myo-inositol (MI), seleno-L-methionine (Se), MI+Se, and resveratrol on C cells of mice exposed to cadmium chloride (Cd Cl2), as no data are currently available on the possible protective effects of these molecules. In contrast, we have previously shown this protective effect against CdCl2 on the thyroid follicles of mice. Ninety-eight C57 BL/6J adult male mice were divided into 14 groups of seven mice each: [i] 0.9% NaCl (vehicle; 1 ml/kg/day i.p.); [ii] Se (0.2 mg/kg/day per os); [iii] Se (0.4 mg/kg/day per os); [iv] MI (360 mg/kg/day per os); [v] Se (0.2 mg/kg/day)+MI; [vi] Se (0.4 mg/kg/day)+MI; [vii] resveratrol (20 mg/kg); [viii] CdCl2 (2 mg/kg/day i.p.)+vehicle; [ix] CdCl2+Se (0.2 mg/kg/day); [x] CdCl2+Se (0.4 mg/kg/day); [xi] CdCl2+MI; [xii] CdCl2+Se (0.2 mg/kg/day)+MI; [xiii] CdCl2+Se (0.4 mg/kg/day)+MI; [xiv] CdCl2+ resveratrol (20 mg/kg). After 14 days, thyroids were processed for histological, immunohistochemical and morphometric evaluation. Compared to vehicle, Cd significantly decreased follicle mean diameter, increased CT-positive cells number, area and cytoplasmic density, and caused the disappearance of TUNEL-positive C cells, namely the disappearance of C cells undergoing apoptosis. Se at either 0.2 or 0.4 mg/kg/day failed to significantly increase follicular mean diameter, mildly decreased CT-positive cells number, area and cytoplasmic density, and was ineffective on TUNEL-positive C cells. Instead, MI alone increased significantly follicular mean diameter and TUNEL-positive cells number, and decreased significantly CT-positive cells number, area and cytoplasmic density. MI+Se 0.2 mg/Kg/day or MI+Se 0.4 mg/Kg/day administration improved all five indices more markedly. Indeed, follicular mean diameter and TUNEL-positive cells number increased significantly, while CT-positive cells number, area and cytoplasmic density decreased significantly. Thus, all five indices overlapped those observed in vehicle-treated mice. Resveratrol improved significantly all the considered parameters, with a magnitude comparable to that of MI alone. In conclusion, the association Myo+Se is effective in protecting the mouse thyroid from the Cd-induced hyperplasia and hypertrophy of C cells. This benefit adds to that exerted by Myo+Se on thyrocytes and testis.